Hadith #5549 - Sunan al-Nasa'i - Habib bin Abi Fadalan/Fadala حبيب بن أبي فضلان/ فضالة المالكي; ibn Abbas; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Sa'id bin Jubayr سعيد بن جبير الأسدي (Sunan al-Nasa'i)
When the prohibition of Khamr was revealed, ‘Umar said: “O Allah, give us a clear ruling on Khamr,” and the Verse in Al-Baqarah was revealed. ‘Umar was called and it was recited to him. Then ‘Umar said: “O Allah, give us a clear ruling on Khamr,” and the Verse in An-Nisa’ was revealed: “O you who believe! Approach not As-Salah (the prayer) when you are in a drunken state”. And when the Iqamah for prayer was said, the caller of the Messenger of Allah would cry out: “O you w
Grade:

Hadith #5550 - Sunan al-Nasa'i - Abdullah bin Numayr عبد الله بن نمير; Abu Sa'id al-Khudri; al-Husain bin Mnswr bin Ja'far الحسين بن منصور بن جعفر; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan al-Nasa'i)
“While I was taking care of a group of people, including my paternal uncles, and I was the youngest of them, a man came and said: ‘Khamr has been forbidden.’ I was taking care of them, and was pouring Fadikh (date-wine) for them. They said: ‘Pour it away.’ So I poured it away.” I (the narrator) said to Anas: “What is that?” He said: “Unripe dates and dried dates.” Abu Bakr bin Anas said: “That was their wine in those days.” And Anas did not deny that.
Grade:

Hadith #5551 - Sunan al-Nasa'i - Abdullah bin Abi Qatada Ibn Rab'i عبد الله بن أبي قتادة الأنصاري السلمي; Abdullah bin Mubarak عبد الله بن المبارك; Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Qatada ibn Rab'i; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“I was pouring (wine) for Abu Talhah, Ubayy bin Ka’b and Abu Dujanah among a group of Ansar when a man came in and said: ‘Something new has happened; the prohibition of Khamr has been revealed.’ So we poured it away.” He said: “The only intoxicant in those days was Fadikh, a mixture of unripe dates and dried dates.” And Anas said: “Khamr was forbidden, and most of their Khamr in those days was Fadikh.”
Grade:

Hadith #5552 - Sunan al-Nasa'i - Abu Qatada ibn Rab'i; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ali bin al-Mubark al-Hna'iy علي بن المبارك الهنائي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Uthman bin 'Umar bin Fars عثمان بن عمر بن فارس; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“When Khamr was forbidden, their drink was (made from) unripe dates and dried dates.”
Grade:

Hadith #5553 - Sunan al-Nasa'i - Abu Sa'id al-Khudri; Ahmed bin Hafs bin 'Abdullah أحمد بن حفص بن عبد الله; al-Ashtar al-Nakha'i الأشتر النخعي; Hafs bin 'Abdullah bin Rashid حفص بن عبد الله بن راشد; Ibrahim bin Tahman إبراهيم بن طهمان; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث; Umar bin Sa'id bin Abi Hussain عمر بن سعيد بن أبي حسين النوفلي (Sunan al-Nasa'i)
“Unripe dates and dried dates are Khamr.”
Grade:

Hadith #5554 - Sunan al-Nasa'i - Ata' bin Abi Rabah عطاء بن أبي رباح; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Ya'qub bin Ibrahim bin Sa'd يعقوب بن إبراهيم بن سعد بن إبراهيم; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan al-Nasa'i)
“Unripe dates and dried dates are Khamr.” Al-A’mash narrated it in Marfu’ form.
Grade:

Hadith #5555 - Sunan al-Nasa'i - Abu Da'ud أبو داود السجستاني الأزدي; Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Ata' bin Abi Rabah عطاء بن أبي رباح; Jabir ibn 'Abdullah; Malik bin Dinar al-Naji مالك بن دينار السامي الناجي (Sunan al-Nasa'i)
The Prophet said: “Raisins and dried dates are Khamr.”
Grade:

Hadith #5556 - Sunan al-Nasa'i - al-Laith bin Sa'd الليث بن سعد; Ata' bin Abi Rabah عطاء بن أبي رباح; Jabir ibn 'Abdullah; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan al-Nasa'i)
The Prophet forbade (mixtures of) Al-Balh and dried dates, and of raisins and dried dates.
Grade:

Hadith #5557 - Sunan al-Nasa'i - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Habib bin Abi Thabit حبيب بن أبي ثابت قيس; ibn Abbas; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان; Sa'id bin Jubayr سعيد بن جبير الأسدي (Sunan al-Nasa'i)
“The Messenger of Allah forbade Ad-Dubba’, Al-Hantam, Al-Muzaffat, and An-Naqir, and (he forbade) mixing Al-Balh with Az-Zahuw.”
Grade:

Hadith #5558 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; ibn Abbas; Ikrama عكرمة; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“The Messenger of Allah forbade Ad-Dubba’, Al-Muzaffat,” – and on one occasion he added: “An-Naqir,” – “and (he forbade) mixing At-Tamr (dried dates) with raisins, and Az-Zahuw with At-Tamr.”
Grade:

Hadith #5559 - Sunan al-Nasa'i - Abdul Rahim bin Sulaiman عبد الرحيم بن سليمان الكناني; Ali bin Sa'id bin Jryr علي بن سعيد بن جرير; Habib bin Abi Fadalan/Fadala حبيب بن أبي فضلان/ فضالة المالكي; ibn Abbas; Sa'id bin Jubayr سعيد بن جبير الأسدي (Sunan al-Nasa'i)
“The Messenger of Allah forbade (mixing) Az-Zahuw and At-Tamr, and raisins and dried dates (At-Tamr).”
Grade:

Hadith #5560 - Sunan al-Nasa'i - al-Husain bin Waqid ak-Mervzi الحسين بن واقد المروزي; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Jabir ibn 'Abdullah (Sunan al-Nasa'i)
The Prophet said: “Do not combine dried dates with raisins, nor Az-Zahuw with ripe dates.”
Grade:

Hadith #5561 - Sunan al-Nasa'i - Abdullah bin Abi Qatada Ibn Rab'i عبد الله بن أبي قتادة الأنصاري السلمي; Abdullah bin Mubarak عبد الله بن المبارك; Abu Qatada ibn Rab'i; Hisham bin 'Urwa هشام بن عروة; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
The Messenger of Allah said: “Do not soak Az-Zahuw and ripe dates together, and do not soak raisins and ripe dates together.”
Grade:

Hadith #5562 - Sunan al-Nasa'i - al-Laith bin Sa'd الليث بن سعد; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan al-Nasa'i)
“The Messenger of Allah forbade mixing dried dates and raisins, and mixing Az-Zahuw and dried dates, and Az-Zahuw and Al-Busr.”
Grade:

Hadith #5563 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Anas ibn Malik; Mukhtar bin Falfal مختار بن فلفل; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Sunan al-Nasa'i)
The Prophet forbade mixing dried dates and raisins, and Al-Busr and ripe dates.
Grade:

Hadith #5564 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Abu Idrees al-Khulani أبو إدريس الخولاني; Hisham bin Hassan al-Azdi هشام بن حسان الأزدي القردوسي; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Sunan al-Nasa'i)
The Messenger of Allah said: “Do not mix raisins and dried dates, nor Al-Busr and dried dates.”
Grade:

Hadith #5565 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Sunan al-Nasa'i)
The Messenger of Allah forbade soaking raisins and dried dates together, and he forbade soaking Al-Busr and dried dates together.
Grade:

Hadith #5566 - Sunan al-Nasa'i - Abdullah bin Abi Qatada Ibn Rab'i عبد الله بن أبي قتادة الأنصاري السلمي; Abu Qatada ibn Rab'i; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“The Messenger of Allah forbade Ad-Dubba’, Al-Hantam, Al-Muzaffat, and An-Naqir, and that Al-Busr be mixed with dried dates, and that raisins be mixed with dried dates, and he wrote to the people of Hajar saying: ‘Do not mix raisins and dried dates together.'”
Grade:

Hadith #5567 - Sunan al-Nasa'i - Abdullah bin Abi Qatada Ibn Rab'i عبد الله بن أبي قتادة الأنصاري السلمي; Abu Qatada ibn Rab'i; Yahya bin Drst bin Ziyad يحيى بن درست بن زياد; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan al-Nasa'i)
“Al-Busr on their own are unlawful and with dried dates they are unlawful.”
Grade:

Hadith #5568 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Abu Sa'id al-Khudri; Isma'il bin Muslim al-Bdy إسماعيل بن مسلم العبدي; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Sunan al-Nasa'i)
“The Messenger of Allah forbade mixing dried dates and raisins, and dried dates and Al-Busr.”
Grade:

Hadith #5569 - Sunan al-Nasa'i - Abu Sa'id al-Khudri; Ali bin Da'ud,Abu al-Mutawakkal al-Naji علي بن داود أبو المتوكل الناجي; Isma'il bin Muslima إسماعيل بن مسلمة بن قعنب الحارثي القعنب; Suh'aib bin Harb شعيب بن حرب (Sunan al-Nasa'i)
“The Messenger of Allah forbade dried dates and raisins, and he forbade dried dates and Al-Busr, if they are soaked together.”
Grade:

Hadith #5570 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Abu Hurairah; Abu Kathir أبو كثير مولى أم سلمة; Ikrama bin 'Ammar عكرمة بن عمار العجلي أبو عمار اليمامي; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Sunan al-Nasa'i)
The Prophet said: “Do not soak Az-Zahuw and ripe dates, and do not soak ripe dates and raisins together.”
Grade:

Hadith #5571 - Sunan al-Nasa'i - Abu Sa'id al-Khudri; Ali bin Da'ud,Abu al-Mutawakkal al-Naji علي بن داود أبو المتوكل الناجي; Isma'il bin Muslima إسماعيل بن مسلمة بن قعنب الحارثي القعنب; Muhammad bin 'Abdullah bin 'Ammar محمد بن عبد الله بن عمار (Sunan al-Nasa'i)
The Messenger of Allah forbade soaking raisins and Al-Busr together, and he forbade soaking Al-Busr and ripe dates together.
Grade:

Hadith #5572 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Hurairah; Abu Kathir أبو كثير مولى أم سلمة; Hameed bin Musa'da bin al-Mubarak حميد بن مسعدة بن المبارك; Sufyan bin Habib al-Basri سفيان بن حبيب البصري; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Sunan al-Nasa'i)
“The Messenger of Allah forbade us to soak two things together when one is more potent than the other. I asked him about Fadikh (a drink made from fresh dates cut open) and he forbade it. He disliked the extra bit on Al-Busr, fearing that that might make it two things, so we used to cut it off.”
Grade:

Hadith #5573 - Sunan al-Nasa'i - Abu Hurairah; Abu Kathir أبو كثير مولى أم سلمة; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي; Ziyad bin Ayoub - Dulwiyya زياد بن أيوب بن زياد دلويه (Sunan al-Nasa'i)
“I saw Anas bin Malik when some Busr which had extra bits were brought to him, and he started to cut them off.”
Grade:

Hadith #5574 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; al-Mughira bin Maqsam المغيرة بن مقسم; Amir al-Sha'bi عامر الشعبي; Ibrahim al-Nakha'i إبراهيم النخعي; Sharayk bin 'Abdullah شريك بن عبد الله النخعي; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Sunan al-Nasa'i)
“Anas used to tell us to cut off the extra bits.”
Grade:

Hadith #5575 - Sunan al-Nasa'i - Habib bin Abi Fadalan/Fadala حبيب بن أبي فضلان/ فضالة المالكي; ibn Umar; Sa'id bin Jubayr سعيد بن جبير الأسدي; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan al-Nasa'i)
Anas would not leave any dates that had become ripe but he would remove them from his Fadikh.
Grade:

Hadith #5576 - Sunan al-Nasa'i - Habib bin Abi Fadalan/Fadala حبيب بن أبي فضلان/ فضالة المالكي; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Sa'id bin Jubayr سعيد بن جبير الأسدي (Sunan al-Nasa'i)
The Messenger of Allah said: “Do not soak Az-Zahuw and ripe dates together, nor Al-Busr and raisins together. Soak each one of them on its own.”
Grade:

Hadith #5577 - Sunan al-Nasa'i - ibn Umar; Sa'id bin Jubayr سعيد بن جبير الأسدي; Sufyan bin 'Uyaynah سفيان بن عيينة; Uthman bin 'Asim bin Husayn عثمان بن عاصم بن حصين أبو حصين (Sunan al-Nasa'i)
The Prophet forbade mixing Az-Zahuw and dried dates, and mixing Al-Busr and dried dates, and he said: “Soak each one of them on its own in vessels that are tied shut.”
Grade:

Hadith #5578 - Sunan al-Nasa'i - Amir al-Sha'bi عامر الشعبي; ibn Umar; Umar ibn al-Khattab; Ya'qub bin Ibrahim bin Sa'd يعقوب بن إبراهيم بن سعد بن إبراهيم; Yahya bin Sa'id bin Hiyan يحيى بن سعيد بن حيان (Sunan al-Nasa'i)
“The Messenger of Allah forbade mixing Al-Busr with dried dates, or raisins with dried dates, or raisins with Al-Busr, and he said: ‘Whoever among you (wants to) drink them, let him drink each one of them on its own: dried dates on their own, or Al-Busr on their own, or raisins on their own.”
Grade:

Hadith #5579 - Sunan al-Nasa'i - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Amir al-Sha'bi عامر الشعبي; ibn Umar; Umar ibn al-Khattab; Yahya bin Sa'id bin Hiyan يحيى بن سعيد بن حيان; Zakaria bin Abi Za'idah زكريا بن أبي زائدة خالد (Sunan al-Nasa'i)
The Prophet forbade mixing Al-Busr with dried dates, or raisins with dried dates, or raisins with Al-Busr, and he said: “Whoever among you (wants to) drink them, let him drink each one on its own.”
Grade:

Hadith #5580 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; Amir al-Sha'bi عامر الشعبي; ibn Umar; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Uthman bin 'Asim bin Husayn عثمان بن عاصم بن حصين أبو حصين (Sunan al-Nasa'i)
“The Messenger of Allah forbade mixing Al-Busr and raisins, and Al-Busr and dried dates, and he said: ‘Soak each one of them on its own.'”
Grade:

Hadith #5581 - Sunan al-Nasa'i - Abdullah bin 'Awn bin Artaban عبد الله بن عون بن أرطبان الخزار; Abdullah bin Mubarak عبد الله بن المبارك; Ibn Sirin محمد بن سيرين الأنصاري; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Sunan al-Nasa'i)
The Prophet forbade soaking dried dates and raisins, and dried dates and Al-Busr, and he said: “Soak raisins on their own, and dried dates on their own, and Al-Busr on their own.”
Grade:

Hadith #5582 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Umar; Nafie' نافع مولى ابن عمر; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Khamr comes from these two.'” Suwaid (one of the narrators) said: “From these two trees: The date palm and the grapevine.”
Grade:

Hadith #5583 - Sunan al-Nasa'i - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Ahmad bin Hanbal أحمد بن حنبل; al-Husain bin Mnswr bin Ja'far الحسين بن منصور بن جعفر; Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Umar; Nafie' نافع مولى ابن عمر (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Khamr comes from these two trees: The date palm and the grapevine.'”
Grade:

Hadith #5584 - Sunan al-Nasa'i - Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Umar; Nafie' نافع مولى ابن عمر; Yahya bin Drst bin Ziyad يحيى بن درست بن زياد (Sunan al-Nasa'i)
“Strong drink is Khamr.”
Grade:

Hadith #5585 - Sunan al-Nasa'i - Ayoub al-Sakhtiyani أيوب السختياني; Ibn Jurayj ابن جريج; ibn Umar; Nafie' نافع مولى ابن عمر (Sunan al-Nasa'i)
“Strong drink is Khamr.”
Grade:

Hadith #5586 - Sunan al-Nasa'i - ibn Mas'ud; ibn Umar; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Nafie' نافع مولى ابن عمر (Sunan al-Nasa'i)
“Strong drink is Khamr.”
Grade:

Hadith #5587 - Sunan al-Nasa'i - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; ibn Umar; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan al-Nasa'i)
“Strong drink is unlawful, and a ‘goodly provision’ (is lawful).”
Grade:

Hadith #5588 - Sunan al-Nasa'i - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan al-Nasa'i)
“I heard ‘Umar, may Allah be pleased with him, delivering a Khutbah on the Minbar of Al-Madinah and he said: ‘O people, on the day that the prohibition of Khamr was revealed, it was made from five things: From grapes, dates, honey, wheat and barley. Khamr is that which overcomes the mind.'”
Grade:

Hadith #5589 - Sunan al-Nasa'i - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس (Sunan al-Nasa'i)
“I heard ‘Umar bin Al-Khattab, may Allah be pleased with him, on the Minbar of the Messenger of Allah , say: ‘The prohibition of Khamr was revealed when it was made from five things: From grapes, wheat, barley, dates and honey.'”
Grade:

Hadith #5590 - Sunan al-Nasa'i - Abu Da'ud أبو داود السجستاني الأزدي; Aisha bint Abi Bakr; al-Qasim ibn Muhammad القاسم بن محمد بن أبي بكر الصديق (Sunan al-Nasa'i)
“Khamr is made from five things: From dates, wheat, barley, honey and grapes.”
Grade:

Hadith #5591 - Sunan al-Nasa'i - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Aisha bint Abi Bakr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan al-Nasa'i)
“A man came to Ibn ‘Umar and said: ‘Our families make drinks for us by soaking (fruits) at night, and in the morning we drink them.’ He said: ‘I forbid you to drink intoxicants whether in small amounts or large. May Allah bear witness that I forbid you to drink intoxicants whether in small amounts or large. May Allah bear witness that the people of Khaibar used to make drinks by soaking such and such, and they called it such and such but it was Khamr. The people of Fadak used to make d
Grade:

Hadith #5592 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Sunan al-Nasa'i)
The Prophet said: “Every intoxicant is unlawful and every intoxicant is Khamr.”
Grade:

Hadith #5593 - Sunan al-Nasa'i - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Aisha bint Abi Bakr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Umar; Ma'mar bin Rashid معمر بن راشد (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Every intoxicant is unlawful and every intoxicant is Khamr.'”
Grade:

Hadith #5594 - Sunan al-Nasa'i - Abdur-Razzaq عبد الرزاق بن همام; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Aisha bint Abi Bakr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Bashr bin al-Sari al-Afwah بشر بن السري أبو عمرو الأفوه; Ma'mar bin Rashid معمر بن راشد (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Every intoxicant is Khamr.'”
Grade:

Hadith #5595 - Sunan al-Nasa'i - Abdullah bin al-Haytham bin 'Uthman عبد الله بن الهيثم بن عثمان; Abu Barda bin Abi Musa al-Asha'ari أبو بردة / الحارث بن أبي موسى الأشعري; Abu Da'ud أبو داود السجستاني الأزدي; Abu Musa al-Asha'ari; Sa'id bin Abi Barda سعيد بن أبي بردة; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Every intoxicant is Khamr and every intoxicant is unlawful.'”
Grade:

Hadith #5596 - Sunan al-Nasa'i - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Abu Barda bin Abi Musa al-Asha'ari أبو بردة / الحارث بن أبي موسى الأشعري; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Abu Musa al-Asha'ari; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق (Sunan al-Nasa'i)
The Prophet said: “Every intoxicant is unlawful and every intoxicant is Khamr.”
Grade:

Hadith #5597 - Sunan al-Nasa'i - Abu Barda bin Abi Musa al-Asha'ari أبو بردة / الحارث بن أبي موسى الأشعري; Abu Musa al-Asha'ari; Sulaiman bin Da'ud bin al-Jarud سليمان بن داود أبو داود الطيالسي; Yahya bin Musa Khat يحيى بن موسى خت (Sunan al-Nasa'i)
The Prophet said: “Every intoxicant is unlawful.”
Grade:

Hadith #5598 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; al-Aswad bin Shayban al-Sadusi الأسود بن شيبان السدوسي (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Every intoxicant is unlawful.'”
Grade:

Hadith #5599 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Ibn Sirin محمد بن سيرين الأنصاري (Sunan al-Nasa'i)
The Messenger of Allah forbade soaking (fruits) in Ad-Dubba’, Al-Muzaffat, An-Naqir, Al-Hantam, and every intoxicant is unlawful.
Grade:

Hadith #5600 - Sunan al-Nasa'i - ibn Umar (Sunan al-Nasa'i)
The Prophet said: “Do not soak (fruits) in Ad-Dubba’, An-Naqir, Al-Hantam, and every intoxicant is unlawful.”
Grade:

Hadith #5601 - Sunan al-Nasa'i - al-S'q bin Hzn الصعق بن حزن; ibn Mas'ud (Sunan al-Nasa'i)
“The Messenger of Allah .”
Grade:

Hadith #5602 - Sunan al-Nasa'i - Abu Barda bin Abi Musa al-Asha'ari أبو بردة / الحارث بن أبي موسى الأشعري; Abu Musa al-Asha'ari; Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Sulaiman bin Da'ud bin al-Jarud سليمان بن داود أبو داود الطيالسي; Talha bin Msrf bin 'Amr طلحة بن مصرف بن عمرو بن كعب (Sunan al-Nasa'i)
The Messenger of Allah was asked about mead and he said: “Every drink that intoxicates is unlawful.” This is the wording of Suwaid.
Grade:

Hadith #5603 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك (Sunan al-Nasa'i)
The Messenger of Allah was asked about mead and he said: “Every drink that intoxicates is unlawful,” and mead is made from honey.
Grade:

Hadith #5604 - Sunan al-Nasa'i - Abu Barda bin Abi Musa al-Asha'ari أبو بردة / الحارث بن أبي موسى الأشعري; Abu Musa al-Asha'ari; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان; Sulaiman bin Abi Sulaiman سليمان بن أبي سليمان (Sunan al-Nasa'i)
The Prophet was asked about mead and he said: “Every drink that intoxicates is unlawful.” And mead is a drink made of honey.
Grade:

Hadith #5605 - Sunan al-Nasa'i - Abdullah bin Tawus عبد الله بن طاوس; Ali bin Nasr bin 'Ali al-Jahdami Older علي بن نصر بن علي الجهضمي الكبير; ibn Umar; Ibrahim bin Nafi' al-Makhzumi إبراهيم بن نافع المخزومي; Nasr bin 'Ali bin Nasr bin 'Ali; Tawus bin Kaysan طاوس (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Every intoxicant is unlawful.'”
Grade:

Hadith #5606 - Sunan al-Nasa'i - ibn Abbas; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan al-Nasa'i)
“The Messenger of Allah sent Mu’adh and me to Yemen. Mu’adh said: ‘You are sending us to a land where the people have many kinds of drinks. What should I drink?’ He said: ‘Drink, but do not drink any intoxicant.'”
Grade:

Hadith #5607 - Sunan al-Nasa'i - Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Every intoxicant is unlawful.'”
Grade:

Hadith #5608 - Sunan al-Nasa'i - al-Dahhak bin 'Uthman bin 'Abdullah الضحاك بن عثمان بن عبد الله بن خالد; Amir bin Sa'd ibn Abi Waqqas عامر بن سعد بن أبي وقاص; Bukayr bin 'Abdullah bin al-Ashj بكير بن عبد الله بن الأشج; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Sa'd ibn Abi Waqqas; Sa'id bin Abi Maryam سعيد بن أبي مريم (Sunan al-Nasa'i)
“I heard ‘Ata’ being asked by a man: ‘We travel and drinks are offered to us in the marketplaces, and we do not know what kind of vessels they were prepared in.’ He said: ‘Every intoxicant is unlawful.’ He repeated the question and he said: ‘Every intoxicant is unlawful.’ He repeated the question and he said: ‘It is as I have told you.'”
Grade:

Hadith #5609 - Sunan al-Nasa'i - al-Dahhak bin 'Uthman bin 'Abdullah الضحاك بن عثمان بن عبد الله بن خالد; al-Walid bin Kathir al-Makhzumi الوليد بن كثير المخزومي; Amir bin Sa'd ibn Abi Waqqas عامر بن سعد بن أبي وقاص; Bukayr bin 'Abdullah bin al-Ashj بكير بن عبد الله بن الأشج; Muhammad bin 'Abdullah bin 'Ammar محمد بن عبد الله بن عمار; Sa'd ibn Abi Waqqas (Sunan al-Nasa'i)
“Every intoxicant is unlawful.”
Grade:

Hadith #5610 - Sunan al-Nasa'i - Abu Hurairah; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Khalid bin 'Abdullah خالد بن عبد الله بن حسين; Sdqh bin Khalid al-Amwy صدقة بن خالد الأموي; Zayd bin Waqd al-Quraishi زيد بن واقد القرشي (Sunan al-Nasa'i)
“Umar bin ‘Abdul-Aziz wrote to us, saying: ‘Do not drink the thickened juice of grapes (obtained by boiling it down) until two-third of it has gone and one-third is left. And every intoxicant is unlawful.'”
Grade:

Hadith #5611 - Sunan al-Nasa'i - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ammar bin Razayq عمار بن رزيق; Sa'sa'a bin Sohan; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan al-Nasa'i)
“Umar bin ‘Abdul-‘Aziz wrote to ‘Adiy bin Artah (saying): ‘Every intoxicant is unlawful.'”
Grade:

Hadith #5612 - Sunan al-Nasa'i - Abdul Wahid bin Ziyad عبد الواحد بن زياد العبدي; Isma'il bin Smy' إسماعيل بن سميع; Malik bin 'Umayr al-Hnfy مالك بن عمير الحنفي الكوفي; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan al-Nasa'i)
The Messenger of Allah said: “Every intoxicant is unlawful.”
Grade:

Hadith #5613 - Sunan al-Nasa'i - Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Do not drink any intoxicant, for I have forbidden all intoxicants.'”
Grade:

Hadith #5614 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد; Tawus bin Kaysan طاوس (Sunan al-Nasa'i)
“The Messenger of Allah sent me to Yemen and I said: ‘O Messenger of Allah, there are drinks there which they call Al-Bit’ (mead) and Al-Mizr (beer).’ He said: ‘What is mead (and beer)?’ I said: ‘A drink made from honey, and beer is made from barley.’ He said: ‘Every intoxicant is unlawful.'”
Grade:

Hadith #5615 - Sunan al-Nasa'i - Ibrahim bin Maysara al-Ta'ifi إبراهيم بن ميسرة الطائفي; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي (Sunan al-Nasa'i)
“The Messenger of Allah delivered a Khutbah and quoted the Verse about Khamr. A man said: ‘O Messenger of Allah, what do you think about Al-Mizr (beer)?’ He said: ‘What is beer?’ He said: ‘A (drink) from grains that is made in Yemen.’ He said: ‘Does it intoxicate?’ He said: ‘Yes.’ He said: ‘Every intoxicant is unlawful.'”
Grade:

Hadith #5616 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Ayana bin 'Abdur rahman bin Jushan عيينة بن عبد الرحمن بن جوشن (Sunan al-Nasa'i)
“I heard Ibn ‘Abbas when he was asked: ‘Advise us about Badhiq (a drink made from the juice of grapes slightly boiled).’ He said: ‘Muhammad came before Badhiq (i.e., it was not known during his time), but everything that intoxicates is unlawful.'”
Grade:

Hadith #5617 - Sunan al-Nasa'i - Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; ibn Umar; Jabla bin Sahaym جبلة بن سحيم; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
The Prophet said: “What intoxicates in large amounts, a small amount of it is unlawful.”
Grade:

Hadith #5618 - Sunan al-Nasa'i - Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
The Prophet said: “I forbid to you small amounts of whatever intoxicates in large amounts.”
Grade:

Hadith #5619 - Sunan al-Nasa'i - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Ayoub al-Sakhtiyani أيوب السختياني; ibn Umar; Sa'id bin Jubayr سعيد بن جبير الأسدي (Sunan al-Nasa'i)
The Prophet forbade a small amount of whatever intoxicates in large amounts.
Grade:

Hadith #5620 - Sunan al-Nasa'i - Amr bin Zararah bin Waqid عمرو بن زرارة بن واقد الكلابي; Ayoub al-Sakhtiyani أيوب السختياني; Sa'id bin Jubayr سعيد بن جبير الأسدي (Sunan al-Nasa'i)
“I know that the Messenger of Allah was fasting, so I prepared some Nabidh for him to break his fast that I had prepared for him in a gourd. I brought it to him and he said: ‘Bring it here.’ So I brought it closer and it was bubbling. He said: ‘Throw it against the wall (throw it away), for this is the drink of one who does not believe in Allah or the Last Day.'”
Grade:

Hadith #5621 - Sunan al-Nasa'i - Abdullah bin Abi Awfa; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sulaiman bin Abi Sulaiman سليمان بن أبي سليمان; Sulaiman bin Da'ud bin al-Jarud سليمان بن داود أبو داود الطيالسي (Sunan al-Nasa'i)
“The Prophet forbade to me to use gold rings, Al-Qassi, Al-Mitharah and Al-Ji’ah (a barley drink).”
Grade:

Hadith #5622 - Sunan al-Nasa'i - Abdullah bin Abi Awfa; Muhammad bin Mansur bin Da'ud محمد بن منصور بن داود الطوسي; Sufyan bin 'Uyaynah سفيان بن عيينة; Sulaiman bin Abi Sulaiman سليمان بن أبي سليمان (Sunan al-Nasa'i)
“Forbid to us, O Commander of the Believers! What the Messenger of Allah forbade me from using Ad-Dubba’ and Al-Hantam.”
Grade:

Hadith #5623 - Sunan al-Nasa'i - al-Hasan al-Basri الحسن البصري; Imran bin Milhan, Abu Raja' al-Atardi عمران بن ملحان أبو رجاء العطاردي; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
(fruits) would be soaked for the Prophet in a small vessel made of stone.
Grade:

Hadith #5624 - Sunan al-Nasa'i - ibn Umar; Ibrahim bin Maysara al-Ta'ifi إبراهيم بن ميسرة الطائفي; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sulaiman bin Da'ud bin al-Jarud سليمان بن داود أبو داود الطيالسي; Tawus bin Kaysan طاوس (Sunan al-Nasa'i)
“A man said to Ibn ‘Umar: ‘Did the Messenger of Allah forbid soaking (fruits) in earthenware jars?’ He said: ‘Yes.’ Tawus said: ‘By Allah, I heard that from him.'”
Grade:

Hadith #5625 - Sunan al-Nasa'i - Abdullah bin Tawus عبد الله بن طاوس; ibn Umar; Ja'far bin Msafr bin Rashid جعفر بن مسافر بن راشد; Tawus bin Kaysan طاوس; Wahayb bin Khalid bin 'Ajlan al-Bahli وهيب بن خالد بن عجلان الباهلي; Yahya bin Hsan يحيى بن حسان (Sunan al-Nasa'i)
“We heard Tawus say: ‘A man came to Ibn ‘Umar and said: Did the Messenger of Allah forbid soaking (fruits) in earthenware jars? He said: ‘Yes.’ Ibrahim added in his Hadith: “And Ad-Dubba’ (gourds).'”
Grade:

Hadith #5626 - Sunan al-Nasa'i - Aisha bint Abi Bakr; al-Aswad bin Yazid الأسود بن يزيد بن قيس النخعي; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Ibrahim al-Nakha'i إبراهيم النخعي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan al-Nasa'i)
“The Messenger of Allah forbade soaking (fruits) in earthenware jars.”
Grade:

Hadith #5627 - Sunan al-Nasa'i - al-Harith bin Suwayd al-Tymy الحارث بن سويد التيمي; Ibrahim bin Yazid - Taym al-Rabab إبراهيم بن يزيد بن شريك تيم الرباب; Muhammad bin Bashar Bindar محمد بن بشار بندار; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan al-Nasa'i)
“The Messenger of Allah forbade Al-Hantam. I (the narrator) said: “What is Al-Hantam?” He said: “The earthenware jar.”
Grade:

Hadith #5628 - Sunan al-Nasa'i - Bkyr bin Ata'a al-Lythy بكير بن عطاء الليثي الكوفي; Muhammad bin Aban bin Wzyr محمد بن أبان بن وزير البلخي; Shababa bin Sawar شبابة بن سوار الفزاري; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“I heard ‘Abdul-‘Aziz – that is, bin Asid At-Tahi from Al-Basrah – say: ‘Ibn Az-Zubair was asked about soaking (fruits) in earthenware jars and he said: “The Messenger of Allah forbade us from that.”
Grade:

Hadith #5629 - Sunan al-Nasa'i - al-Laith bin Sa'd الليث بن سعد; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Anas ibn Malik; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan al-Nasa'i)
“We asked Ibn ‘Umar about Nabidh made in an earthenware jar and he said: ‘The Messenger of Allah forbade it.’ He said: ‘Ibn ‘Umar spoke the truth.’ I said: ‘What is an earthenware jar?’ He said: ‘Anything that is made of clay.'”
Grade:

Hadith #5630 - Sunan al-Nasa'i - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Muhammad bin Mansur bin Da'ud محمد بن منصور بن داود الطوسي; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan al-Nasa'i)
“I was with Ibn ‘Umar when he was asked about Nabidh made in an earthenware jar. He said: ‘The Messenger of Allah forbade it.’ I said: ‘What is an earthenware jar?’ He said: ‘Anything that is made of clay.'”
Grade:

Hadith #5631 - Sunan al-Nasa'i - ibn Umar; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan al-Nasa'i)
“I heard Ibn Abi Awfa say: ‘The Messenger of Allah forbade Nabidh made in green earthenware jars.’ I said: ‘And white ones?’ He said: ‘I do not know.'”
Grade:

Hadith #5632 - Sunan al-Nasa'i - ibn Umar; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Sa'id bin Abi Sa'id; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“I heard Ibn Abi Awfa say: ‘The Messenger of Allah forbade Nabidh made in green and white earthenware jars.'”
Grade:

Hadith #5633 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Abu Sa'id al-Khudri; Ali bin Da'ud,Abu al-Mutawakkal al-Naji علي بن داود أبو المتوكل الناجي; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Sunan al-Nasa'i)
“I asked Al-Hasan about Nabidh made in earthenware jars – is it unlawful? He said: ‘(It is) unlawful. One who would not lie narrated to us that the Messenger of Allah forbade Nabidh made in Al-Hantam, Ad-Dubba’ (gourds), Al-Muzaffat and An-Naqir.'”
Grade:

Hadith #5634 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; ibn Umar; Maharab bin Dithar محارب بن دثار; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
The Messenger of Allah forbade Ad-Dubba’ (gourds).
Grade:

Hadith #5635 - Sunan al-Nasa'i - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; ibn Mas'ud; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
The Messenger of Allah forbade Ad-Dubba’ (gourds).
Grade:

Hadith #5636 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Jmylh bint 'Aabad Rwt جميلة بنت عباد; Zaynab bint Nasr زينب بنت نصر (Sunan al-Nasa'i)
“The Messenger of Allah forbade Ad-Dubba’ (gourds) and Al-Muzaffat.”
Grade:

Hadith #5637 - Sunan al-Nasa'i - Abu Hurairah; al-Husain bin Dhakwan al-Mua'lam الحسين بن ذكوان المعلم المكتب; Muhammad bin Ziyad محمد بن زياد القرشي (Sunan al-Nasa'i)
The Prophet forbade Ad-Dubba’ (gourds) and Al-Muzaffat.
Grade:

Hadith #5638 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; al-Qasim bin al-Fadl bin Ma'dan القاسم بن الفضل بن معدان; Thmamh bin Hzn ثمامة بن حزن (Sunan al-Nasa'i)
The Prophet forbade Ad-Dubba’ and Al-Muzaffat.
Grade:

Hadith #5639 - Sunan al-Nasa'i - Aisha bint Abi Bakr; Ishaq bin Suwayd bin Hubayra إسحاق بن سويد بن هبيرة; Mu'adhah bint 'Abdullah معاذة بنت عبد الله; Ziyad bin Ayoub - Dulwiyya زياد بن أيوب بن زياد دلويه (Sunan al-Nasa'i)
The Messenger of Allah forbade soaking (fruits) in Ad-Dubba’ (gourds) and Al-Muzaffat.
Grade:

Hadith #5640 - Sunan al-Nasa'i - Aisha bint Abi Bakr; Ishaq bin Suwayd bin Hubayra إسحاق بن سويد بن هبيرة; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Mu'adhah bint 'Abdullah معاذة بنت عبد الله; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
“The Messenger of Allah forbade soaking (fruits) in Ad-Dubba’ (gourds) and Al-Muzaffat.”
Grade:

Hadith #5641 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك (Sunan al-Nasa'i)
The Messenger of Allah forbade Al-Muzaffat and squashes.
Grade:

Hadith #5642 - Sunan al-Nasa'i - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Anas ibn Malik; Mukhtar bin Falfal مختار بن فلفل; Ziyad bin Ayoub - Dulwiyya زياد بن أيوب بن زياد دلويه (Sunan al-Nasa'i)
The Messenger of Allah forbade Ad-Dubba’ (gourds), Al-Hantam and An-Naqir.
Grade:

Hadith #5643 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; ibn Umar; Mnswr bin Hyan منصور بن حيان; Sa'id bin Jubayr سعيد بن جبير الأسدي; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
The Messenger of Allah forbade drinking from green pitchers, gourds and vessels carved from wood.
Grade:

Hadith #5644 - Sunan al-Nasa'i - Asma' bint Yazid bin al-Sakan; ibn Mas'ud; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي (Sunan al-Nasa'i)
“The Messenger of Allah forbade Ad-Dubba’ (gourds), Al-Hantam and Al-Muzaffat.”
Grade:

Hadith #5645 - Sunan al-Nasa'i - Amr bin Murrah bin 'Abdullah عمرو بن مرة بن عبد الله بن طارق; ibn Umar; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Zadhan Abu 'Umar زاذان أبو عمر (Sunan al-Nasa'i)
“The Messenger of Allah forbade earthenware jars, Ad-Dubba’ (gourds), Al-Muzaffat containers.”
Grade:

Hadith #5646 - Sunan al-Nasa'i - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Abu Hurairah; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس (Sunan al-Nasa'i)
“I heard the Messenger of Allah forbidding drinks made in Dubba’ (gourds), Hantam or Muzaffat, that were not oil or vinegar.”
Grade:

Hadith #5647 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan al-Nasa'i)
“The Messenger of Allah forbade Ad-Dubba’ (gourds), Al-Hantam, An-Naqir, and Al-Muzaffat.”
Grade:

Hadith #5648 - Sunan al-Nasa'i - Abdul Malik bin Aby عبد الملك بن أبي سليمان; Ishaq bin Yusuf bin Mrdas إسحاق بن يوسف بن مرداس; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan al-Nasa'i)
“I met ‘Aishah and asked her about Nabidh. She said: ‘The delegation of ‘Abdul-Qais came to the Messenger of Allah forbade them to soak (fruits) in Ad-Dubba’ (gourds), An-Naqir, Al-Muqayyar, and Al-Hantam.'”
Grade:

Hadith #5649 - Sunan al-Nasa'i - Abdul Malik bin 'Umayr al-Qabti عبد الملك بن عمير بن سويد القبطي; Jabir ibn 'Abdullah; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan al-Nasa'i)
“He forbade Ad-Dubba’ (gourds) specifically.”
Grade:

Hadith #5650 - Sunan al-Nasa'i - Amr bin al-Aswad al-Ansi عمرو بن الأسود العنسي; ibn Mas'ud; Ibrahim bin Sa'id al-Juhari إبراهيم بن سعيد الجوهري; Mujahid bin Jabir مجاهد بن جبر; Sufyan bin 'Uyaynah سفيان بن عيينة; Sulaiman bin Abi Muslim al-Ahwal سليمان بن أبي مسلم سليمان الأحول (Sunan al-Nasa'i)
“Mu’adhah narrated to me from ‘Aishah, that the Messenger of Allah forbade Nabidh made in An-Naqir, Al-Muqayyar, Ad-Dubba’, and Al-Hantam.” And in the narration of Ibn ‘Ulayyah, Ishaq said: “And Hunaidah mentioned from ‘Aishah similar to the narration of Mu’adhah, and she named earthenware containers. I said to Hunaidah: ‘Did you hear her say earthenware containers?’ She said: ‘Yes.'”
Grade:

Hadith #5651 - Sunan al-Nasa'i - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; al-Zubair bin Ady al-Hmdany الزبير بن عدي الهمداني اليامي; Ammar bin Razayq عمار بن رزيق; Burayda bin al-Husayb (Sunan al-Nasa'i)
“I met ‘Aishah, may Allah be pleased with her, in Al-Khuraibah, and I asked her about the dregs and she forbade them to me and she said: ‘Soak (the fruit) at night and drink it in the morning, and tie the vessel closed.’ And she forbade me from using Ad-Dubba’ (gourds), An-Naqir, Al-Muzaffat, and Al-Hantam.”
Grade:

Hadith #5652 - Sunan al-Nasa'i - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Burayda bin al-Husayb; Maharab bin Dithar محارب بن دثار; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان (Sunan al-Nasa'i)
“The Messenger of Allah forbade Al-Muzaffat.”
Grade:

Hadith #5653 - Sunan al-Nasa'i - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; al-Hasan bin Muhammad bin A'yn الحسن بن محمد بن أعين; Burayda bin al-Husayb; Maharab bin Dithar محارب بن دثار; Zubayd bin al-Harith زبيد بن الحارث اليامي; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan al-Nasa'i)
He heard Ibn ‘Umar and Ibn ‘Abbas testify that the Messenger of Allah recited this Verse: “And whatsoever the Messenger (Muhammad) gives you, take it; and whatsoever he forbids you, abstain (from it).”
Grade:

Hadith #5654 - Sunan al-Nasa'i - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Burayda bin al-Husayb; Hammad bin Salama حماد بن سلمة; Hmad bin Abi Sulaiman حماد بن أبي سليمان مسلم (Sunan al-Nasa'i)
A paternal uncle of hers whose name was Anas said: “Ibn ‘Abbas said: Does not Allah say: “And whatsoever the Messenger (Muhammad) gives you, take it; and whatsoever he forbids you, abstain (from it).’? He said: ‘Yes.’ He said: ‘Does not Allah say: ‘It is not for a believer, man or woman, when Allah and His Messenger have decreed a matter that they should have any option in their decision?’ I said: ‘Yes.’ He said: ‘I bear witness that the Prophet of Allah forbade An-Naqir
Grade:

Hadith #5655 - Sunan al-Nasa'i - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Burayda bin al-Husayb; Isa bin 'Ubaid bin Malik عيسى بن عبيد بن مالك (Sunan al-Nasa'i)
“I asked ‘Abdullah bin ‘Umar: ‘Tell me of something that you heard from the Messenger of Allah forbade Al-Hantam, which are what you call earthenware jars. And he forbade Ad-Dubba’ which are what you call squash. And he forbade An-Naqir, which are hollowed-out date palm wood. And he forbade Al-Muzaffat which are (Al-Muqayyar) vessels daubed with tar.'”
Grade:

Hadith #5656 - Sunan al-Nasa'i - Jabir ibn 'Abdullah; Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin 'Abdullah bin al-Zubair محمد بن عبد الله أبو أحمد الزبيري; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Umar bin Sa'd bin 'Ubaid عمر بن سعد بن عبيد أبو داود (Sunan al-Nasa'i)
“The Messenger of Allah forbade the delegation of ‘Abdul-Qais, when they came to him, Ad-Dubba’, An-Naqir, Al-Muzaffat, and large water-skins that are cut from the top and can no longer be closed. He said: ‘Make Nabidh in your water-skins, and close them and drink it sweet.’ One of them said: ‘O Messenger of Allah, give me permission concerning something like this. He said: ‘If you make it like this,’ and he gestured with his hand, showing him how.”
Grade:

Hadith #5657 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan al-Nasa'i)
“The Messenger of Allah could not find a water-skin in which to make Nabidh, it would be made for him in a small vessel of stone.”
Grade:

Hadith #5658 - Sunan al-Nasa'i - Abdullah/Abu Bakr bin Hafs bin 'Umar عبد الله بن حفص بن عمر - أبو بكر; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“(Fruit) would be soaked for the Messenger of Allah forbade Ad-Dubba’ (gourds), An-Naqir, and Al-Muzaffat.”
Grade:

Hadith #5659 - Sunan al-Nasa'i - Abu Bakr bin 'Abdur Rahman أبو بكر بن عبد الرحمن بن الحارث بن هشام; Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Aqil bin Khalid bin 'Aqil عقيل بن خالد بن عقيل الأيلي; Isa bin Hammad bin Muslim, Zaghba عيسى بن حماد بن مسلم أبو موسى زغبة (Sunan al-Nasa'i)
The Messenger of Allah forbade Ad-Dubba’ (gourds), An-Naqir, earthenware jars, and Al-Muzaffat.
Grade:

Hadith #5660 - Sunan al-Nasa'i - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Hurairah; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan al-Nasa'i)
The Prophet granted a concession allowing earthenware jars that are not coated with pitch.
Grade:

Hadith #5661 - Sunan al-Nasa'i - Abdur Rahman bin Abi Na'm عبد الرحمن بن أبي نعم; al-Mughira bin Maqsam المغيرة بن مقسم; ibn Umar; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘I used to forbid you (to store) the sacrificial meat, but now eat it and store it; and whosoever wants to visit graves (may do so), for they are a reminder of the Hereafter; and drink but avoid all intoxicants.”
Grade:

Hadith #5662 - Sunan al-Nasa'i - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Shababa bin Sawar شبابة بن سوار الفزاري (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘I used to forbid you to visit graves, but (now) visit them. And I forbade you (to keep) the sacrificial meat for three days, but now keep whatever you wish. And I forbade Nabidh to you, unless it was (made) in a water skin, but now drink from all kinds of vessels but do not drink any intoxicant.'”
Grade:

Hadith #5663 - Sunan al-Nasa'i - Abu Barda bin Abi Musa al-Asha'ari أبو بردة / الحارث بن أبي موسى الأشعري; Abu Musa al-Asha'ari; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘I used to forbid three things to you: Visiting graves, but now visit them, and may visiting them increase you in goodness; and I forbade you (to store) the sacrificial meat for more than three days, but now eat whatever you wish of it. And I forbade to you drinks in (certain kinds of ) vessels, but now drink from whatever vessel you wish, but do not drink any intoxicant.'”
Grade:

Hadith #5664 - Sunan al-Nasa'i - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘I used to forbid certain kinds of vessels to you. Now soak (fruits) in whatever you wish, but beware of any intoxicant.'”
Grade:

Hadith #5665 - Sunan al-Nasa'i - al-Hakam bin 'Utayba الحكم بن عتيبة; Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Khlf bin Khlyfh خلف بن خليفة; Masrouq bin al-Ajda' مسروق بن الأجدع; Mnswr bin Zadhan منصور بن زاذان; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Shaqayq bin Salmah al-Asadi شقيق بن سلمة الأسدي أبو وائل الكوفي (Sunan al-Nasa'i)
While the Messenger of Allah was walking, he approached some people and heard a confused noise coming from them. He said: “What is this noise?” They said: “O Messenger of Allah, they have a drink that they drink.” He sent for those people and said: “In what do you soak (fruit – to make that drink)?” They said: “We soak (fruits) in vessels carved from wood and gourds, and we have no water skins (that can be closed).” He said: “Do not drink except from a vessel that can be tie
Grade:

Hadith #5666 - Sunan al-Nasa'i - Abdur Rahman ibn al-Harith; Abu Bakr bin 'Abdur Rahman أبو بكر بن عبد الرحمن بن الحارث بن هشام; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Umar; Ma'mar bin Rashid معمر بن راشد; Uthman ibn 'Affaan (Sunan al-Nasa'i)
When the Messenger of Allah said: “Then there is no harm.”
Grade:

Hadith #5667 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Abdur Rahman ibn al-Harith; Abu Bakr bin 'Abdur Rahman أبو بكر بن عبد الرحمن بن الحارث بن هشام; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Uthman ibn 'Affaan; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan al-Nasa'i)
“On the night on which he was taken on the Night Journey (Al-Isra’), two cups, of wine and milk, were brought to the Messenger of Allah . He looked at them and chose the milk. Jibril, peace be upon him, said to him: ‘Praise be to Allah Who has guided you to the Fitrah. If you have chosen the wine, your Ummah would have gone astray.'”
Grade:

Hadith #5668 - Sunan al-Nasa'i - al-'Ala' bin al-Msyb bin Rafa'i العلاء بن المسيب بن رافع; Fdyl bin Sulaiman al-Nmyry فضيل بن سليمان النميري; ibn Umar; Mujahid bin Jabir مجاهد بن جبر; Sryj bin Yonus bin Ibrahim سريج بن يونس بن إبراهيم (Sunan al-Nasa'i)
The Prophet said: “People among my Ummah will drink Khamr, calling it by another name.”
Grade:

Hadith #5669 - Sunan al-Nasa'i - Abdul Rahim bin Sulaiman عبد الرحيم بن سليمان الكناني; Abdullah bin 'Amr bin al-'Aas; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان; Mujahid bin Jabir مجاهد بن جبر; Yazid bin Abi Ziyad يزيد بن أبي زياد; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘The adulterer is not a believer at the moment when he is committing adultery, and the wine drinker is not a believer at the moment when he is drinking wine, and the thief is not a believer at the moment when he is stealing, and the robber is not a believer at the moment when he is robbing and people are looking on.'”
Grade:

Hadith #5670 - Sunan al-Nasa'i - Abdullah bin al-Dayli; Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; al-Qasim bin Zakaria bin Dinar القاسم بن زكريا بن دينار القرشي; Amr bin 'Uthman عمرو بن عثمان بن عفان; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Mua'wiya bin 'Amr bin al-Mhlb معاوية بن عمرو بن المهلب بن عمرو; Rabi'a bin Yazid al-Damashqi ربيعة بن يزيد الدمشقي (Sunan al-Nasa'i)
The Prophet said: “The adulterer is not a believer at the moment when he is committing adultery, and the thief is not a believer at the moment when he is stealing, and the wine drinker is not a believer at the moment when he is drinking wine, and the robber is not a believer at the moment when he is robbing and taking something valuable by force while the Muslims are looking at it.'”
Grade:

Hadith #5671 - Sunan al-Nasa'i - al-Harith bin Mskyn bin Muhammad الحارث بن مسكين بن محمد; ibn Umar; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Nafie' نافع مولى ابن عمر; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Whoever drinks Khamr, whip him; then if he drinks (again), whip him; then if he drinks (again), whip him; then if he drinks (again), kill him.'”
Grade:

Hadith #5672 - Sunan al-Nasa'i - Abdullah bin 'Amr bin al-'Aas; Jaban; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Salm bin Abi al-Ja'd سالم بن أبي الجعد; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
The Messenger of Allah said: “If he becomes drunk, whip him; then if he becomes drunk, whip him; then if he becomes drunk, whip him.” Then he said concerning the fourth time, “Strike his neck (i.e., kill him).”
Grade:

Hadith #5673 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Umar; Nafie' نافع مولى ابن عمر (Sunan al-Nasa'i)
That his father used to say: “I do not see any difference between drinking Khamr and worshipping this column instead of Allah the Mighty and Sublime.”
Grade:

Hadith #5674 - Sunan al-Nasa'i - Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Umar; Nafie' نافع مولى ابن عمر; Yahya bin Drst bin Ziyad يحيى بن درست بن زياد (Sunan al-Nasa'i)
Ibn Ad-Dailami rode looking for ‘Abdullah bin ‘Amr bin Al-‘As. Ibn Ad-Dailami said: “I entered upon him and said: ‘O ‘Abdullah bin ‘Amr, did you hear the Messenger of Allah say: If a man among my Ummah drinks Khamr, Allah will not accept his Salah for forty days.'”
Grade:

Hadith #5675 - Sunan al-Nasa'i - al-Hasan bin Yahya bin Hisham الحسن بن يحيى بن هشام; ibn Mas'ud (Sunan al-Nasa'i)
“If a judge accepts a gift he has consumed something unlawful, and if he accepts a bribe, that takes him to the level of Kufr.” Masruq said: “Whoever drinks Khamr, he has committed (an act of) Kufr, and his Kufr is that his Salah does not count.”
Grade:

Hadith #5676 - Sunan al-Nasa'i - Abdul A'ala bin Hamad bin Nasr al-Bahli عبد الأعلى بن حماد بن نصر الباهلي النرسي; Abdur-Razzaq عبد الرزاق بن همام; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan al-Nasa'i)
“I heard ‘Uthman, may Allah be pleased with him, say: ‘Avoid Khamr for it is the mother of all evils. There was a man among those who came before you who was a devoted worshipper. An immoral woman fell in love with him. She sent her slave girl to him, saying: We are calling you to bear witness. So he set out with her slave girl, and every time he entered a door, she locked it behind him, until he reached a beautiful woman who has with her a boy and a vessel of wine. She said: ‘By Allah,
Grade:

Hadith #5677 - Sunan al-Nasa'i - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Abu Burda bin Niyar; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Smak bin Hrb bin Aws سماك بن حرب بن أوس (Sunan al-Nasa'i)
“I heard ‘Uthman say: ‘Avoid Khamr for it is the mother of all evils. There was a man among those who came before you who was a devoted worshipper and used to stay away from people.'” And he mentioned something similar. He said: “Avoid Khamr for, by Allah, it can never coexist with Faith, but soon one of them will expel the other.”
Grade:

Hadith #5678 - Sunan al-Nasa'i - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Burayda bin al-Husayb; Muhammad bin Isma'il bin Ibrahim محمد بن إسماعيل بن إبراهيم بن مقسم; Sharayk bin 'Abdullah شريك بن عبد الله النخعي; Smak bin Hrb bin Aws سماك بن حرب بن أوس; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“Whoever drinks Khamr and does not get intoxicated, his Salah will not be accepted so long as any trace of it remains in his belly or his veins, and if he dies he will die a Kafir. If he becomes intoxicated his Salah will not be accepted for 40 nights, and if he dies during them, he will die a Kafir.” (Sahih Mawquf)
Grade:

Hadith #5679 - Sunan al-Nasa'i - Aisha bint Abi Bakr; Smak bin Hrb bin Aws سماك بن حرب بن أوس; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan al-Nasa'i)
The Prophet said: “Whoever drinks Khamr and puts it in his belly, Allah will not accept his Salah for seven (days), if he dies during them” – Muhammad bin Adam (One of the narrators) said: “he will die a Kafir. If he was too intoxicated to offer any of the obligatory” – Ibn Adam said: “or recite Qur’an, his Salah will not be accepted for 40 days, and if he dies during them,” And Ibn Adam said: “He will die a Kafir.”
Grade:

Hadith #5680 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Jasrah bint Dajaja جسرة بنت دجاجة; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Sunan al-Nasa'i)
“I entered upon ‘Abdullah bin ‘Amr bin Al-‘As when he was in a garden of his in At-Ta’if called Al-Waht. He was walking and holding hands with a young man of Quraish who was suspected of drinking Khamr. He said: ‘I heard the Messenger of Allah say: Whoever drinks Khamr once, his repentance will not be accepted for 40 days, then if he repents, Allah will accept his repentance. If he does it again, his repentance will not be accepted for 40 days, then if he repents, Allah will accept
Grade:

Hadith #5681 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Aisha bint Abi Bakr; Ali bin al-Mubark al-Hna'iy علي بن المبارك الهنائي; Krymh bint Hmam كريمة بنت همام; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Sunan al-Nasa'i)
The Messenger of Allah said: “Whoever drinks Khamr in this world and does not repent from that, will be denied it in the Hereafter.”
Grade:

Hadith #5682 - Sunan al-Nasa'i - Aban bin Sm'h أبان بن صمعة; Aisha bint Abi Bakr; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان (Sunan al-Nasa'i)
The Prophet said: “No one who reminds others of his favors, no one who is disobedient to his parents and no drunkard, will enter Paradise.”
Grade:

Hadith #5683 - Sunan al-Nasa'i - Abdul Warith bin Sa'id bin Dhakwan عبد الوارث بن سعيد بن ذكوان; Abdullah ibn Shaddad; ibn Abbas; Ubaidullah bin 'Umar al-Qawariri عبيد الله بن عمر القواريري (Sunan al-Nasa'i)
The Prophet said: “Whoever drinks Khamr in this world and dies addicted to it, and not having repented, will not drink it in the Hereafter.”
Grade:

Hadith #5684 - Sunan al-Nasa'i - Abdullah ibn Shaddad; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; ibn Abbas; Sryj bin Yonus bin Ibrahim سريج بن يونس بن إبراهيم (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Whoever drinks Khamr in this world and dies addicted to it, will not drink it in the Hereafter.'”
Grade:

Hadith #5685 - Sunan al-Nasa'i - Abdullah ibn Shaddad; Ahmad bin Hanbal أحمد بن حنبل; al-Husain bin Mnswr bin Ja'far الحسين بن منصور بن جعفر; ibn Abbas; Mas'ar bin Kadam مسعر بن كدام; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Muhammad bin 'Ubaidullah bin Sa'id محمد بن عبيد الله بن سعيد أبو عون الثقفي; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“Whoever dies addicted to Khamr will have boiling water thrown in his face when he departs this world.”
Grade:

Hadith #5686 - Sunan al-Nasa'i - Abdullah ibn Shaddad; Ahmad bin Hanbal أحمد بن حنبل; al-Husain bin Mnswr bin Ja'far الحسين بن منصور بن جعفر; ibn Abbas; Muhammad bin 'Ubaidullah bin Sa'id محمد بن عبيد الله بن سعيد أبو عون الثقفي; Sharayk bin 'Abdullah bin Abi Namr شريك بن عبد الله بن أبي نمر (Sunan al-Nasa'i)
“‘Umar, may Allah be pleased with him, banished Rabi’ah bin Umaiyah to Khaibar for drinking Khamr, and he went and joined Heraclius and became a Christian. ‘Umar, may Allah be pleased with him, said: ‘I will never expel any Muslim after this.'”
Grade:

Hadith #5687 - Sunan al-Nasa'i - Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Drink from vessels but do not become intoxicated.'”
Grade:

Hadith #5688 - Sunan al-Nasa'i - Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; al-Nadr bin Shumayl al-Maazni النضر بن شميل المازني أبو الحسن النحوي; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Salmah bin Kahayl al-Hadrami سلمة بن كهيل بن حصين; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Wahb bin Jarir bin Hazim bin Zayd وهب بن جرير بن حازم بن زيد (Sunan al-Nasa'i)
The Messenger of Allah forbade Ad-Dubba’, Al-Hantam, An-Naqir, and Al-Muzaffat.
Grade:

Hadith #5689 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Ayana bin 'Abdur rahman bin Jushan عيينة بن عبد الرحمن بن جوشن; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Sunan al-Nasa'i)
‘Aishah said: “Drink but do not become intoxicated.”
Grade:

Hadith #5690 - Sunan al-Nasa'i - Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Abbas; Sa'id bin Jubayr سعيد بن جبير الأسدي; Ubaidullah bin 'Umar al-Qawariri عبيد الله بن عمر القواريري (Sunan al-Nasa'i)
“I heard ‘Aishah when some people asked her about Nabidh, saying we soak dates in the morning and drink it in the evening, or we soak them in the evening and drink them in the morning. She said: ‘I do not permit any intoxicant even if it were bread or even if it were water.’ She said that three times.”
Grade:

Hadith #5691 - Sunan al-Nasa'i - Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Nasr bin 'Imran bin Isam نصر بن عمران بن عصام; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“Karimah bint Hammam told me that she heard ‘Aishah, the Mother of the Believers, say: ‘You have been forbidden Ad-Dubba’ (gourds), you have been forbidden Al-Hantam, you have been forbidden Al-Muzaffat.’ Then she turned to women and said: ‘Beware of green earthenware jars, and if the water in your clay vessels intoxicates you, do not drink it.'”
Grade:

Hadith #5692 - Sunan al-Nasa'i - Abu Da'ud أبو داود السجستاني الأزدي; Qurrah bin Khalid al-Sadusi قرة بن خالد السدوسي (Sunan al-Nasa'i)
“The Messenger of Allah used to forbid all intoxicants.” And they use the narration of ‘Abdullah bin Shaddad from ‘Abdullah bin ‘Abbas.
Grade:

Hadith #5693 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; ibn Abbas; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي (Sunan al-Nasa'i)
“Khamr was forbidden in small or large amounts, as was every kind of intoxicating drink.”
Grade:

Hadith #5694 - Sunan al-Nasa'i - al-'Awwam bin Hushab العوام بن حوشب بن يزيد; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Ziyad bin Ayoub - Dulwiyya زياد بن أيوب بن زياد دلويه (Sunan al-Nasa'i)
“Khamr was forbidden in and of itself in small or large amounts, as was every kind of intoxicating drink.”
Grade:

Hadith #5695 - Sunan al-Nasa'i - ibn Umar; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Sulaiman bin Abi Sulaiman سليمان بن أبي سليمان (Sunan al-Nasa'i)
“Khamr was forbidden in and of itself, in small or large amounts, as was every kind of intoxicating drink.”
Grade:

Hadith #5696 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; ibn Umar; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة; Zayd bin Jubayra bin Mahmud زيد بن جبيرة (Sunan al-Nasa'i)
“Khamr was forbidden in small or large amounts, as was every kind of drink that intoxicates.”
Grade:

Hadith #5697 - Sunan al-Nasa'i - ibn Umar; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة; Zayd bin Jubayra bin Mahmud زيد بن جبيرة (Sunan al-Nasa'i)
“I asked Ibn ‘Abbas, when he was leaning back against the Ka’bah, about Badhaq (a drink made from the juice of grapes slightly boiled). He said: ‘Muhammad came before Badhaq (i.e., it was not known during his time), but everything that intoxicates in unlawful.'” He said: “I was the first of the ‘Arabs to ask him.”
Grade:

Hadith #5698 - Sunan al-Nasa'i - ibn Mas'ud; Ibn Sirin محمد بن سيرين الأنصاري; ibn Umar; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي (Sunan al-Nasa'i)
“Whoever would like to regard as forbidden that which Allah and His Messenger regard as forbidden, let him regard Nabidh as forbidden.”
Grade:

Hadith #5699 - Sunan al-Nasa'i - al-Harith bin Mskyn bin Muhammad الحارث بن مسكين بن محمد; ibn Umar; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Nafie' نافع مولى ابن عمر (Sunan al-Nasa'i)
“A man said to Ibn ‘Abbas: ‘I am a man from Khurasan, and our land is a cold land. We have a drink that is made from raisins and grapes and other things, and I am confused about it.’ He mentioned different kinds of drinks to him and mentioned many, until I thought that he had not understood him. Ibn ‘Abbas said to him: ‘You have told me too many. Avoid whatever intoxicates, whether it is made of dates, raisins or anything else.'”
Grade:

Hadith #5700 - Sunan al-Nasa'i - ibn Umar; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Mqatl bin Hyan al-Nbty مقاتل بن حيان النبطي; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب (Sunan al-Nasa'i)
“Nabidh made from Al-Busr is forbidden and is not permissible.”
Grade:

Hadith #5701 - Sunan al-Nasa'i - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Husain bin Mnswr bin Ja'far الحسين بن منصور بن جعفر; ibn Umar; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Yazid bin Harun يزيد بن هارون (Sunan al-Nasa'i)
“I used to interpret between Ibn ‘Abbas and the people. A woman came to him and asked him about Nabidh made in earthenware jars, and he forbade it. I said: ‘O Abu ‘Abbas, I make a sweet Nabidh in a green earthenware jar; when I drink it, my stomach makes noises.’ He said: ‘Do not drink it even if it is sweeter than honey.'”
Grade:

Hadith #5702 - Sunan al-Nasa'i - ibn Mas'ud; Rqyh bint 'Umar رقية بنت عمر (Sunan al-Nasa'i)
“I said to Ibn ‘Abbas that my grandmother makes Nabidh in an earthenware jar and it is sweet. If I drink a lot of it and sit with people, I am worried that they will find out. He said: ‘The delegation of ‘Abdul-Qais came to the Messenger of Allah and he said: Welcome to a delegation that is not disgraced or filled with regret. They said: O Messenger of Allah, the idolators are between us and you, and we can only reach you during the sacred months. Tell us of something which, if we do it
Grade:

Hadith #5703 - Sunan al-Nasa'i - Abu Mas'ud al-Badri; Khalid bin Sa'd al-Kwfy خالد بن سعد الكوفي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Yaman al-Jly يحيى بن يمان العجلي (Sunan al-Nasa'i)
“I asked Ibn ‘Abbas: ‘I have a small jar in which I make Nabidh and when it has bubbled and settled down again, I drink it.’ He said: ‘For how long you have been drinking that?’ He said: ‘For twenty years'” – or he said: ‘for forty years.’ He said: ‘For a long time you have been quenching your thirst with something forbidden.'”
Grade:

Hadith #5704 - Sunan al-Nasa'i - Abu Hurairah; Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Zayd bin Waqd al-Quraishi زيد بن واقد القرشي (Sunan al-Nasa'i)
“While he was at the Rukn, I saw a man bring a cup to the Messenger of Allah in which there was Nabidh. He gave the cup to him and he raised it to his mouth, but he found it to be strong, so he gave it back to him and a man among the people said: ‘O Messenger of Allah, is it unlawful?’ He said: ‘Bring the man to me.’ So he was brought to him. He took the cup from him and called for water. He poured it into the cup, which he raised to his mouth and frowned. Then he called for more wate
Grade:

Hadith #5705 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Abu Rafi'; al-Sry bin Yahya bin Iyas السري بن يحيى بن إياس; Umar ibn al-Khattab (Sunan al-Nasa'i)
A similar report was narrated from ‘Abdul-Malik bin Nafi’ from Ibn ‘Umar, from the Prophet .
Grade:

Hadith #5706 - Sunan al-Nasa'i - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري (Sunan al-Nasa'i)
A man asked about drinks and he said: “Avoid everything that intoxicates.”
Grade:

Hadith #5707 - Sunan al-Nasa'i - Isma'il bin Abi Khalid al-Ahmsi إسماعيل بن أبي خالد الأحمسي; Muhammad bin Jahada محمد بن جحادة; Qays bin Abi Hazim قيس بن أبي حازم; Utba bin Frqd; Zuhayr bin Harb زهير بن حرب بن شداد أبو خثيمة (Sunan al-Nasa'i)
“I asked Ibn ‘Umar about drinks and he said: ‘Avoid everything that intoxicates.'”
Grade:

Hadith #5708 - Sunan al-Nasa'i - al-Harith bin Mskyn bin Muhammad الحارث بن مسكين بن محمد; al-Sa'ib bin Yazid bin Akht Namr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Umar ibn al-Khattab (Sunan al-Nasa'i)
“Intoxicants are unlawful in small or large amounts.”
Grade:

Hadith #5709 - Sunan al-Nasa'i - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Amarah bin Ghazya bin al-Harith عمارة بن غزية بن الحارث; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan al-Nasa'i)
“Every intoxicant is Khamr and every intoxicant is unlawful.”
Grade:

Hadith #5710 - Sunan al-Nasa'i - Abdullah bin 'Awn bin Artaban عبد الله بن عون بن أرطبان الخزار; al-Nu'man bin Bashir ibn Sa'd; Amir al-Sha'bi عامر الشعبي; Hameed bin Musa'da bin al-Mubarak حميد بن مسعدة بن المبارك; Yazid bin Zari' يزيد بن زريع (Sunan al-Nasa'i)
The Messenger of Allah said: “Allah has forbidden Khamr, and every intoxicant is unlawful.”
Grade:

Hadith #5711 - Sunan al-Nasa'i - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Bryd bin Abi Maryam بريد بن أبي مريم مالك; Muhammad bin Aban bin Wzyr محمد بن أبان بن وزير البلخي; Rabi'ya bin Shyban al-Sa'dy ربيعة بن شيبان السعدي; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Every intoxicant is unlawful and every intoxicant is Khamr.'”
Grade:

Hadith #5712 - Sunan al-Nasa'i - Abdullah bin Tawus عبد الله بن طاوس; Ma'mar bin Rashid معمر بن راشد; Tawus bin Kaysan طاوس (Sunan al-Nasa'i)
“I was under the care of Ibn ‘Umar, and raisins would be soaked for him and he would drink them in the morning, then the raisins would be left to dry, and other raisins would be added to them, and water would be poured on top of them, and he would drink that in the morning. Then the day after he would throw them away.”
Grade:

Hadith #5713 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Mus'ub bin Sa'd ibn Abi Waqqas مصعب بن سعد بن أبى وقاص الزهرى (Sunan al-Nasa'i)
“The Prophet became thirsty around the Ka’bah so he called for a drink. Some Nabidh was brought in a water skin and he smelled it and frowned. He said: ‘Bring me a bucket of Zamzam (water).’ He poured it over it and drank some. A man said: ‘Is it unlawful, O Messenger of Allah?’ He said: ‘No.'”
Grade:

Hadith #5714 - Sunan al-Nasa'i - Ibn Sirin محمد بن سيرين الأنصاري; ibn Umar (Sunan al-Nasa'i)
“I knew that the Messenger of Allah was fasting on certain days, so I prepared some Nabidh for him to break his fast, and made it in a gourd. When evening came I brought it to him, and said: ‘O Messenger of Allah, I knew that you were fasting today, so I prepared this Nabidh for you to break your fast.’ He said: ‘Bring it to me, O Abu Hurairah.’ I brought it to him, and it turned out to be something bubbling. He said: ‘Take this and throw it against the wall (throw it away), for thi
Grade:

Hadith #5715 - Sunan al-Nasa'i - Ibrahim al-Nakha'i إبراهيم النخعي; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Suwayd bin Ghaflah bin Awsajah سويد بن غفلة بن عوسجة (Sunan al-Nasa'i)
‘Umar bin Al-Khattab, may Allah be pleased with him, said: “If you fear that Nabidh may be too strong, then weaken it with water.” ‘Abdullah (one of the narrators) said: “Before it gets strong.”
Grade:

Hadith #5716 - Sunan al-Nasa'i - ibn Mas'ud; Lahaaq bin Hameed bin Sa'id لاحق بن حميد بن سعيد أبو مجلز; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي (Sunan al-Nasa'i)
“Thaqif welcomed ‘Umar with a drink. He called for it, but when he brought it close to his mouth, he did not like it. He called for water to weaken it, and said: ‘Do like this.'”
Grade:

Hadith #5717 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Abdullah bin Yazid bin Zayd; Hisham bin 'Urwa هشام بن عروة; Ibn Sirin محمد بن سيرين الأنصاري (Sunan al-Nasa'i)
“The Nabidh that ‘Umar bin Al-Khattab used to drink had turned to vinegar.”
Grade:

Hadith #5718 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; al-Mughira bin Maqsam المغيرة بن مقسم; Ali ibn Abi Talib; Amir al-Sha'bi عامر الشعبي; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي (Sunan al-Nasa'i)
‘Umar bin Al-Khattab went out t them and said: “I noticed the smell of drink on so-and-so, and he said that he had drunk At-Tila’ (thickened juice of grapes). I am asking about what he drank. If it was an intoxicant I will flog him.” So ‘Umar bin Al-Khattab, may Allah be pleased with him, flogged him, carrying out the Hadd punishment in full.
Grade:

Hadith #5719 - Sunan al-Nasa'i - Muhammad bin Abi 'Adi محمد بن أبي عدي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan al-Nasa'i)
A man from (the tribe of) Jaishan, who are from Yemen, came and asked the Messenger of Allah said: “Every intoxicant is unlawful. Allah, the Mighty and Sublime, has promised the one who drinks intoxicants that He will give him to drink from the mud of Khibal.” They said: “O Messenger of Allah, what is the mud of Khibal?” He said: “The sweat of the people of Hell,” or he said: “The juice of the people of Hell.”
Grade:

Hadith #5720 - Sunan al-Nasa'i - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Hammad bin Salama حماد بن سلمة; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan al-Nasa'i)
“I heard the Messenger of Allah say: ‘That which is lawful is clear and that which is unlawful is clear, but between them there are matters which are doubtful.'” And sometimes he said: “But between them are matters that are not as clear. I will describe the likeness of that for you. Allah, the Mighty and Sublime, has a sanctuary and the sanctuary of Allah is that which He has forbidden. Whoever grazes around the sanctuary will soon transgress into the sanctuary. And whoever approaches a
Grade:

Hadith #5721 - Sunan al-Nasa'i - Abu Musa al-Asha'ari; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; ibn Umar; Isma'il bin Abi Khalid al-Ahmsi إسماعيل بن أبي خالد الأحمسي; Qays bin Abi Hazim قيس بن أبي حازم (Sunan al-Nasa'i)
“I said to Al-Hasan bin ‘Ali, may Allah be pleased with him: ‘What did you memorize from the Messenger of Allah ?’ He said: I memorized from him: ‘Leave that which makes you doubt for that which does not make you doubt.'”
Grade:

Hadith #5722 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan al-Nasa'i)
He disliked to sell raisins to one who would use them to make Nabidh.
Grade:

Hadith #5723 - Sunan al-Nasa'i - Ma'n bin 'Isa bin Yahya معن بن عيسى بن يحيى; Mu'awiya bin Salah bin Hadayr معاوية بن صالح بن حدير; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري (Sunan al-Nasa'i)
“Sa’d had many grapevines and he had someone looking after them for him. (The vines) bore many grapes, and that man wrote to him (saying): ‘I am afraid that the grapes will be wasted; what do you think if I squeeze them to make juice? Sa’d wrote to him (saying): ‘When this letter of mine reaches you, leave my land, for by Allah I cannot trust you with anything ever agin.’ So he made him leave his land.”
Grade:

Hadith #5724 - Sunan al-Nasa'i - al-Hasan al-Basri الحسن البصري; ibn Umar; Imran bin Milhan, Abu Raja' al-Atardi عمران بن ملحان أبو رجاء العطاردي; Yazid bin Zari' يزيد بن زريع (Sunan al-Nasa'i)
“Sell it as juice to one who will make At-Tila’ (thickened grape juice) with it, and not Khamr (wine) with it.”
Grade:

Hadith #5725 - Sunan al-Nasa'i - Bashyr bin al-Mhajr بشير بن المهاجر; ibn Umar (Sunan al-Nasa'i)
“Umar bin Al-Khattab wrote to some of his workers saying: ‘Give to the Muslims thickened grape juice when two thirds of it have gone and one-third is left.'”
Grade:

Hadith #5726 - Sunan al-Nasa'i - Anas bin Sirin أنس بن سيرين الأنصاري; Anas ibn Malik; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Sa'd bin Aws al-Bsy سعد بن أوس العبسي; Waki' bin al-Jarrah وكيع بن الجراح (Sunan al-Nasa'i)
“I saw the letter of ‘Umar bin Al-Khattab to Abu Musa (in which he said): ‘A caravan came to me from Ash-Sham carrying a thick black paint like the pitch that is daubed on camels. I asked them how long they cooked it, and they told me that they cooked it until it was reduced by two-third. So the bad two-third had gone, one-third to take away evil and one-third to take away the bad smell. So let those who are with you drink it.”
Grade:

Hadith #5727 - Sunan al-Nasa'i - ibn Mas'ud (Sunan al-Nasa'i)
“Umar bin Al-Khattab, may Allah be pleased with him, wrote to us (saying): ‘Cook your drinks until the share of the Shaitan is gone, for he has two (shares) and you have one.'”
Grade:

Hadith #5728 - Sunan al-Nasa'i - Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Makhul al-Shami/al-Damashiqi مكحول الشامي (Sunan al-Nasa'i)
“Ali, may Allah be pleased with him, used to give the people thickened grape juice into which flies would fall and not be able to get out again.”
Grade:

Hadith #5729 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك (Sunan al-Nasa'i)
“I asked Sa’eed: ‘What is the drink that ‘Umar bin Al-Khattab, may Allah be pleased with him, regarded as permissible?’ He said: ‘That which has been cooked until two-third has gone and one-third is left.'”
Grade:

Hadith #5730 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Ata' bin Abi Rabah عطاء بن أبي رباح; ibn Abbas (Sunan al-Nasa'i)
Abu Ad-Darda’ used to drink that of which two-third had gone and one-third was left.
Grade:

Hadith #5731 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Aqil bin Khalid bin 'Aqil عقيل بن خالد بن عقيل الأيلي; Haywat bin Sharih bin Safwan حيوة بن شريح بن صفوان التجيبي; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan al-Nasa'i)
He used to drink thickened grape juice that of which two-third had gone and one-third was left.
Grade:

Hadith #5732 - Sunan al-Nasa'i - ibn Umar; Ibrahim al-Nakha'i إبراهيم النخعي (Sunan al-Nasa'i)
“I heard Sa’eed bin Al-Musayyab say, when a Bedouin asked him about a drink that had been cooked and reduced by half: ‘No, not until two-third has gone and one-third is left.'”
Grade:

Hadith #5733 - Sunan al-Nasa'i - Abdul Malik bin 'Umayr al-Qabti عبد الملك بن عمير بن سويد القبطي; Abdullah bin Mubarak عبد الله بن المبارك (Sunan al-Nasa'i)
“When At-Tila’ (thickened grape juice) has been cooked and reduced to one-third, then there is nothing wrong with it.”
Grade:

Hadith #5734 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Amir al-Sha'bi عامر الشعبي; Hammad bin Salama حماد بن سلمة (Sunan al-Nasa'i)
“I asked Al-Hasan about At-Tila’ (thickened grape juice) that has been reduced to half. He said: ‘Do not drink it.'”
Grade:

Hadith #5735 - Sunan al-Nasa'i - Abdullah bin al-Dayli; Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Amr bin 'Uthman bin Sa'id bin Kahtir عمرو بن عثمان بن سعيد بن كثير; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد (Sunan al-Nasa'i)
“I asked Al-Hasan about juice that has been cooked. He said: ‘That which has been cooked until two-third of it has gone and one-third is left.'”
Grade:

Hadith #5736 - Sunan al-Nasa'i - Abdullah bin al-Dayli; Dmrh bin Rabi'ya al-Flstyny ضمرة بن ربيعة الفلسطيني أبو عبد الله; Fyrwz al-Dylmy; Sulaiman bin Abi Sulaiman سليمان بن أبي سليمان (Sunan al-Nasa'i)
“I heard Anas bin Malik say: ‘The Shaitan disputed with Nuh, peace be upon him, concerning the grapevine. One said: “This is for me,” and the other said: “This is for me.” Then they agreed that Nuh would have one-third and the Shaitan would have two-thirds.'”
Grade:

Hadith #5737 - Sunan al-Nasa'i - ibn Abbas; Sulaiman bin Syf bin Yahya سليمان بن سيف بن يحيى; Ya'la bin 'Ubaid bin Umayya al-Tanafasi يعلى بن عبيد بن أبي أمية الطنافسي (Sunan al-Nasa'i)
“Umar bin ‘Abdul-‘Aziz wrote to us (saying): ‘Do not drink At-Tila’ (thickened grape juice) until two-third of it are gone and one-third remains, and every intoxicant is unlawful.'”
Grade:

Hadith #5738 - Sunan al-Nasa'i - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; ibn Abbas; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Sharayk bin 'Abdullah شريك بن عبد الله النخعي; Yahya bin 'Ubaid al-Bahrani يحيى بن عبيد البهراني; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan al-Nasa'i)
“Every intoxicant is unlawful.”
Grade:

Hadith #5739 - Sunan al-Nasa'i - ibn Abbas; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan al-Nasa'i)
“I was with Ibn ‘Abbas when a man came to him and asked him about juice. He said: ‘Drink that which is fresh.’ He said: ‘I cooked a drink on the fire and I am not sure about it.’ He said: ‘Did you drink it before you cooked it?’ He said: ‘No.’ He said: ‘Fire does not make permissible something that is forbidden.'” (Sahih Mawquf)
Grade:

Hadith #5740 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; ibn Umar; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan al-Nasa'i)
“I heard Ibn ‘Abbas say: ‘By Allah, fire does not make anything permissible or forbidden.'” He said: “Then he explained what he meant by ‘it does not make permissible’ as referring to what they said about At-Tila’ (thickened grape juice), and he explained what he said about ‘it does not make forbidden’ as referring to performing Wudu’ after eating something that has been touched by fire.”
Grade:

Hadith #5741 - Sunan al-Nasa'i - Abu Ja'far al-Qari' أبو جعفر القارئ; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; ibn Mas'ud (Sunan al-Nasa'i)
“Drink juice so long as it does not have any foam.”
Grade:

Hadith #5742 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك (Sunan al-Nasa'i)
“I asked Ibrahim about juice and he said: ‘Drink it, unless it bubbles, so long as it doesn’t change.'”
Grade:

Hadith #5743 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Abu 'Uthman al-Nahdi عبد الرحمن بن مل - أبو عثمان النهدي; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي (Sunan al-Nasa'i)
He said, concerning juice: “Drink it unless it is bubbling.”
Grade:

Hadith #5744 - Sunan al-Nasa'i - ibn Umar; Ma'mar bin Rashid معمر بن راشد; Qatada قتادة; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan al-Nasa'i)
“Drink it for three days unless it bubbles.”
Grade:

Hadith #5745 - Sunan al-Nasa'i - Da'ud bin Abi Hnd داود بن أبي هند; ibn Umar; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan al-Nasa'i)
“I came to the Messenger of Allah and said: ‘O Messenger of Allah, we have grapevines and Allah, the Mighty and Sublime, has revealed that Khamr (wine) is forbidden, so what should we do?’ He said: ‘Make raisins.’ I said: ‘What should we do with the raisins?’ He said: ‘Soak them in the morning and drink them in the evening, and soak them in the evening and drink them in the morning.’ I said: ‘Can we leave it until it gets stronger?’ He said: ‘Do not put it in clay vessel
Grade:

Hadith #5746 - Sunan al-Nasa'i - ibn Umar; Qatada قتادة; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“We said: ‘O Messenger of Allah, we have grapevines; what should we do with them?’ He said: ‘Make raisins.’ We said: ‘What should we do with the raisins?’ He said: ‘Soak them in the morning and drink them in the evening, and soak them in the evening and drink them in the morning.’ I said: ‘Can we leave it until it gets stronger?’ He said: ‘Do not put it in clay vessels, rather put it in skins, for if it stays there for a long time, it will turn into vinegar.'”
Grade:

Hadith #5747 - Sunan al-Nasa'i - Fdyl bin 'Amr al-Fqymy فضيل بن عمرو الفقيمي; Ibrahim al-Nakha'i إبراهيم النخعي; Ubaidullah bin 'Umar al-Qawariri عبيد الله بن عمر القواريري; Yahya bin Zakaria bin Abi Zaida يحيى بن زكريا بن أبي زائدة (Sunan al-Nasa'i)
“Nabidh would be made for the Messenger of Allah and he would drink it in the morning, and on the following morning. Then on the evening before the third day, if there was anything left in the vessel, they would not drink it and it would be thrown away.”
Grade:

Hadith #5748 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; al-Mughira bin Maqsam المغيرة بن مقسم; Ibrahim al-Nakha'i إبراهيم النخعي; Najih bin 'Abdur Rahman نجيح بن عبد الرحمن السندي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan al-Nasa'i)
Raisins would be soaked for the Messenger of Allah and he would drink it that day, the following day, and the day after that.
Grade:

Hadith #5749 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Ibrahim al-Nakha'i إبراهيم النخعي; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan al-Nasa'i)
“Nabidh of raisins would be made for the Messenger of Allah at night, and he would put it in a water skin and drink it during the next day, the day after, and the day after that. At the end of the third day, he would give it to others to drink, or drink it himself, and if anything was left the following morning, he would pour it away.”
Grade:

Hadith #5750 - Sunan al-Nasa'i - Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي (Sunan al-Nasa'i)
Nabidh of raisins would be made for him in a water skin in the morning, and he would drink it that night, and it would be made for him in the evening, and he would drink it in the morning. He would wash out the water skins and not leave any pieces or anything in them. Nafi’ said: “We used to drink it like honey.”
Grade:

Hadith #5751 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Hammad bin Usamah حماد بن أسامة - أبو أسامة (Sunan al-Nasa'i)
“I asked Abu Ja’far about Nabidh and he said: ” ‘Ali bin Husain, may Allah be pleased with him, would have Nabidh made for him at night, and he would drink it in the morning, and he would have Nabidh made in the morning and he would drink it at night.'”
Grade:

Hadith #5752 - Sunan al-Nasa'i - Hammad bin Usamah حماد بن أسامة - أبو أسامة (Sunan al-Nasa'i)
“I heard Sufyan being asked about Nabidh. He said: ‘Make Nabidh at night and drink it in the morning.'”
Grade:

Hadith #5753 - Sunan al-Nasa'i - al-Rabi' bin Sulaiman الربيع بن سليمان; Anas ibn Malik; Asad bin Musa - Asad al-Sunnah أسد بن موسى بن إبراهيم - أسد السنة; Hammad bin Salama حماد بن سلمة; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan al-Nasa'i)
Umm Al-Fadl sent word to Anas bin Malik, asking him about Nabidh made in an earthenware jar. He told her about his son An-Nadr, who used to make Nabidh in an earthenware jar in the morning and drink it in the evening.
Grade:

Hadith #5754 - Sunan al-Nasa'i - Abdur Rahman bin Abza; Dhar bin 'Abdullah al-Marhabi ذر بن عبد الله المرهبي; ibn Mas'ud; Sa'id bin 'Abdur Rahman bin Abza سعيد بن عبد الرحمن بن أبزي; Salmah bin Kahayl al-Hadrami سلمة بن كهيل بن حصين; Sufyan bin 'Uyaynah سفيان بن عيينة; Ubayy ibn Ka'b (Sunan al-Nasa'i)
He disliked putting the dregs of Nabidh into (new) Nabidh lest it become strong because of the dregs.
Grade:

Hadith #5755 - Sunan al-Nasa'i - Ahmed bin 'Ali al-Nmyry أحمد بن علي النميري; ibn Mas'ud; Ibn Sirin محمد بن سيرين الأنصاري; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي; Ubaida bin 'Amr al-Salamani عبيدة بن عمرو; Ubaidullah bin 'Umar al-Qawariri عبيد الله بن عمر القواريري (Sunan al-Nasa'i)
“The dregs are what intoxicates.”
Grade:

Hadith #5756 - Sunan al-Nasa'i - Abdullah bin 'Awn bin Artaban عبد الله بن عون بن أرطبان الخزار; Abdullah bin Mubarak عبد الله بن المبارك; Ibn Sirin محمد بن سيرين الأنصاري; Ubaida bin 'Amr al-Salamani عبيدة بن عمرو (Sunan al-Nasa'i)
“Khamr is so called because it is left until the good parts are gone and the dregs remain.” And he disliked everything that was made by using dregs (by adding new materials to the dregs).
Grade:

Hadith #5757 - Sunan al-Nasa'i - Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي (Sunan al-Nasa'i)
“They used to think that whoever drank something and became intoxicated from it, it was not befitting for him to go back and drink more of the same.”
Grade:

Hadith #5758 - Sunan al-Nasa'i - Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي (Sunan al-Nasa'i)
“There is nothing wrong with Nabidh Al-Bukhtuj.”
Grade:

Hadith #5759 - Sunan al-Nasa'i (Sunan al-Nasa'i)
“I asked Ibrahim: ‘We take the dregs of Khamr or Tila’ (thickened grape juice) and clean them, then we soak it with raisins for three days, then we strain it and leave it until it matures, then we drink it.’ He said: ‘That is Makruh.'”
Grade:

Hadith #5760 - Sunan al-Nasa'i (Sunan al-Nasa'i)
“May Allah have mercy on Ibrahim. Other scholars had strict views on Nabidh but he was lenient.”
Grade:

Hadith #5761 - Sunan al-Nasa'i (Sunan al-Nasa'i)
“I have never found any sound report, giving a concession on intoxicants, except the report narrated from Ibrahim.”
Grade:

Hadith #5762 - Sunan al-Nasa'i (Sunan al-Nasa'i)
“I heard Abu Usamah say: ‘I never saw any man more assiduous in seeking knowledge than ‘Abdullah bin Al-Mubarak, not in Ash-Sham, Egypt, Yemen or the Hijaz.'”
Grade:

Hadith #5763 - Sunan al-Nasa'i (Sunan al-Nasa'i)
Umm Sulaim had a wooden cup and she said: “I gave the Messenger of Allah all kinds of things to drink in it: Water, honey, milk and Nabidh.”
Grade:

Hadith #5764 - Sunan al-Nasa'i (Sunan al-Nasa'i)
“I asked Ubayy bin Ka’b about Nabidh, and he said: ‘Drink water, drink honey, drink Sawiq (barley gruel) and drink milk that you have been nourished with since childhood.’ I repeated the question and he said: ‘Is it wine you want? Is it wine you want?'”
Grade:

Hadith #5765 - Sunan al-Nasa'i (Sunan al-Nasa'i)
“The people have invented new drinks and I do not know what they are. I have not drunk anything for 20 years (or he said: 40 years) except water and Sawiq (barley gruel), and he did not mention Nabidh.”
Grade:

Hadith #5766 - Sunan al-Nasa'i (Sunan al-Nasa'i)
“The people have invented drinks and I do not know what they are. I have not drunk anything for 20 years except water, milk and honey.”
Grade:

Hadith #5767 - Sunan al-Nasa'i (Sunan al-Nasa'i)
“Talhah said to the people of Al-Kufah concerning Nabidh: ‘It is a test whereby a young man may benefit but an old man may be harmed.’ If there was a wedding among them, Talhah and Zubaid would offer milk and honey to drink. It was said to Talhah: ‘Why don’t you offer Nabidh?’ He said: ‘I would not like a Muslim to become intoxicated because of me.'”
Grade:

Hadith #5768 - Sunan al-Nasa'i (Sunan al-Nasa'i)
“Ibn Shubrumah would not drink anything except water and milk.”
Grade: